(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
I consider Alice Munro to be one of our most important writers of psychological fiction. She has the courage to emphatically revive the psychology of the Romanticist Movement, to stick up for Freud when that’s still justifiable, and to blend the two approaches with her own insights and technical genius, to come to her own bold conclusions.The day that I realized that she’s describing the terrors and the horrors of the patriarchal world was the day that I began to understand Munro. She doesn’t underline her social message. She doesn’t underline any message. Neither Chekhov nor Munro would be so vulgar as to state the message the way you’d put it in a slogan, or on a flag. That’s not art. Art gives us a situation in which we feel the message, if we’re sensitive to it. One of the great things about Munro is that she forces us to participate in her stories. We have to see connections she’s not going to point them out for us.A typical situation in a Munro story is that a woman’s predicament, in some family or social situation—something that seems trivial, or everyday-ish—will explode into a major problem. For example, in “Runaway,” Carla lies to her husband, Clark, telling him how her employer’s husband lured her to his bed. This sexually excites them both, initially, but then leads to something more threatening. Carla tries to solve the issue by running away, and the choices she makes lead her and Clark to discovery.